Hubungan Self-Efficacy dengan Kemampuan Pengukuran pada Anak Usia 5-6 Tahun di TK Two M Kid’s Kecamatan Tampan Kota Pekanbaru - Emiyarti Emiyarti; Yeni Solfiah; Zulkifli N (Journal on Education, 2024)
Based on the results of observations made by researchers regarding the measurement ability of children aged 5-6 years at Two M Kid's Kindergarten, Tampan District, Pekanbaru City, they tend to experience difficulties, so the researcher aims to determine the relationship between self-efficacy and measurement ability in children. The type of research carried out was quantitative correlation, using a saturated sampling technique. So, the entire population, namely children in Two M Kid's Kindergarten aged 5-6 years, totaling 45 children were used as samples. This research uses observation sheets to collect data. Data analysis uses product moment correlation analysis and t test with SPSS ver 25. The results of the correlation relationship show a sig value of 0.00 so the sig value is smaller than 0.05 so it is said to be correlated. Meanwhile, the Pearson correlation value is 0.655, included in the interval 0.60-0.799 with a strong level of relationship. It is known that the t tabel has a value of 2.0180 with t hitung calculated of 5.87, thus there is a significant relationship between self-efficacy and the measuring ability of children aged 5-6 years at Two M Kid's Kindergarten, Tampan District, Pekanbaru City.